2010
DOI: 10.3109/14767050903061769
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal diagnosis of Chiari malformation with syringomyelia in the second trimester

Abstract: Routine anatomic ultrasound performed in the second trimester has a detection rate of approximately 70-90% for fetal congenital abnormalities (Nyberg and Souter, J Ultrasound Med 2001;6:655-674). The central nervous system abnormalities are one of the most common ones detected. Chiari malformation is among the CNS abnormalities diagnosed in the fetal period (Bianchi et al., Fetology - diagnosis and management of the fetal patient, McGraw-Hill, 2000). The Arnold-Chiari malformation was first described in 1883 b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 2 publications
0
11
0
Order By: Relevance
“…The cerebel-lar hemisphere and the vermis, which form the roof of the fourth ventricle, grow rapidly (Kapur et al 2009), and during the second trimester the tentorium of the cerebellum is being shaped. Some abnormalities may arise during this process (Iruretagoyena et al 2010), such as COACH syndrome and Dandy-Walker syndrome (Alexiou et al 2010).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The cerebel-lar hemisphere and the vermis, which form the roof of the fourth ventricle, grow rapidly (Kapur et al 2009), and during the second trimester the tentorium of the cerebellum is being shaped. Some abnormalities may arise during this process (Iruretagoyena et al 2010), such as COACH syndrome and Dandy-Walker syndrome (Alexiou et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Ultrasound examination is the main technique used to evaluate the fetal brain, having the advantages of reliability, low cost, portability and real-time visualization. Some abnormalities in the posterior cranial fossa, including cerebellar tonsillar hernia (Iruretagoyena et al 2010), can be identified using ultrasound from the second trimester. Rutten et al (2009) measured the volume of the fetal cerebellum with 3D-ultrasound from 20 weeks of gestational age (GA) to determine the asymmetry between the left and right sides.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The central nervous system abnormalities are one of the most common ones detected. Chiari malformation is one among the CNS abnormalities diagnosed by prenatal sonography [6]. The obvious sonographic findings are the frontal bone scalloping (lemon sign) and absent cerebellum or abnormal anterior curvature of the cerebellar hemispheres (banana sign) [7].…”
Section: Discussionmentioning
confidence: 99%
“…[4,5,13-15], there is only a scant literature on the pathology or mechanisms of syrinx formation in the human fetus. This is perhaps surprising, as large post-mortem series on the subject mention syrinx formation as not infrequent in fetal, neonatal and paediatric Chiari II malformations [14,15] and there is an ultrasound report of detection of syringomyelia in a pre-term fetus [16], although a large radiological series demonstrates detection by MRI be very unusual and late in gestation [17]. …”
Section: Introductionmentioning
confidence: 99%